SZŰKÜLŐ ABLAKOK - A MAGYAR KOLLEKTÍV IDEGRENDSZER METAFORÁJA - Szilárdi , Réka (Kultúratudományi Szemle, 2025)
Narrowing windows - A metaphor for the Hungarian collective nervous system The following paper draws parallels between the Hungarian socio-psychological forms of collective threat experience and the concept of chronic traumatisation. The linking of the two entirely different processes takes place in the metaphorical space, i.e. the aim is not to establish a one-to-one or a cause-and-effect correspondence but to unpack the analogy through the conceptual system of the identifier and the identified, which allows us to illustrate certain characteristics of Hungarian social functioning, such as the distinctive collective sense of victimhood or the fixed and persistent state of fear. In this identification, István Bibó's concept of community hysteria and the neurological mechanisms of the complex post-traumatic syndrome (C-PTSD) are analogous, besides Lak off's concept of conceptual metaphor, according to which metaphor is a form of interpreting the world, which also plays a key role.